Correlation for Predicting Heat Transfer Characteristics of A Helical Oscillating Heat Pipe (HOHP) at Normal Operating Conditions - Donmuang, Amorn; Chompookham, Teerapat (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The helical oscillating heat pipe (HOHP) is a high heat transfer heat exchanger with high flexibility in its installation and can therefore be used in a wide variety of applications. In this study, the effect of various parameters on the heat transfer rates of HOHP were used to establish a correlation equation for use in the heat flux prediction, the dimensionless parameters studied were rv/rl, Bo, Nu, We, Ja, Pr, Fr, Co, Ga, Bi, Wo, Oh, and Ku. Â Experiments were conducted to find out their effects on the heat transfer rates of copper HOHP with internal diameters were 2.03, 3.5, and 4.5 mm. The lengths of evaporator and condenser sections were equal at 1500, 2000, and 2500 mm. The pitch coils were 10, 15, and 20 mm. The working fluids used were R134a, ethanol, and water with the filling ratios were 30%, 50%, and 80% of the total internal volume. The temperature of evaporator section were varied between 60, 70, and 80Â°C within normal operating conditions in a vertical position. The results of the experiment showed that the internal diameter, lengths of evaporator/condenser sections, pitch coil, type of working fluid, filling ratio and temperature of evaporator section affected the heat transfer rates of the HOHP. The results of dimensionless parameters can establish the correlation equation to predict the heat flux for the HOHP as shown in this paper. In addition, the results of this research can be applied in the designing and construction of HOHP heat exchangers.